(untitled) (Italian Journal of Public Health, 2008)
Background: The measurement and definition of disability is difficult due to its objective and subjective characteristics. In Italy, three different perspectives have been developed during the last 40 years. These various perspectives have had an effect, not only on how to measure disability, but also on policies to improve the social integration of people with disabilities. Methods: This paper examines the various conceptual models behind the definition of disability and the differences in the estimated number of persons with disabilities. In addition, it analyses in accordance with the International Classification of Functioning, disability and health, the European and international initiatives undertaken to harmonize the definitions of disability. Discussion: There are various bodies and central government agencies that either have management data or carry out statistical systematic surveys and disability surveys. Statistically speaking, the worst aspect of this scenario is that it creates confusion and uncertainty among the end users of this data, namely the policy makers. At international level the statistical data on disability is scarcely comparable among countries, despite huge efforts on behalf of international organisations to harmonize classifications and definitions of disability. Conclusions: Statistical and administrative surveys provide information flows using a different definition and label based on a conceptual model that reflects the time period in which they were implemented. The use of different prescriptive definitions of disability produces different counts of persons with disabilities in Italy. For this reason it is important to interpret the data correctly and choose the appropriate cross section that best represents the population on which to focus attention.